O uso de vídeo e jogo educativos como instrumento de ensino e divulgação da Astronomia - Souza, Thauane Lima de (2016)
Currently, due to the various technological options, the vast access to information and the demotivation of some students, much is discussed in the literature about the way of teaching so that it becomes diversified and attractive. The teacher / classroom model with traditional teaching has leaved to be the main medium in the teaching-learning process. Faced with this new educational paradigm, the need arises to seek strategies that increase the interest, the motivation and consequently the level of learning of the students. In this sense, we have the ludic forms of teaching, such as the application of didactic games, which are increasingly present in the school environment. From this context, a didactic game, entitled "Space Track" and an educational video called "Unraveling the Universe", was created. The theme is about Planets and Dwarf Planets, Eclipse, Seasons of the Year, General Astronomy and Constellations. In particular, these tools can be used in both formal and non-formal learning environments. In this work the product was applied in five classes of Elementary School and four of the High School of the Colégio Estadual Ferreira Pinto. The survey of prior knowledge and learning after the implementation of activities was carried out through pre- and post-tests on the above topics.